En tredje vej for teologisk etik? - Andersen, Svend (Dansk Teologisk Tidsskrift, 2015)
The article is a review of Ulrik B. Nissen’s higher doctoral degree thesis, which deals with Bonhoeffer’s ethics seen within the Lutheran tradition. By means of the exposition of Luther’s and Bonhoeffer’s ethical thoughts, Nissen aims at formulating a third position between universality and specificity, particularly in regard to the role of Christian/religious arguments in public discourse. As a conceptual instrument for grasping the theological foundation of the alleged third way, Nissen uses Chalcedonian Christology and communicatio idiomatum. The reviewer claims that even if there is, in Lutheran ethics, a combination of a specific Christian and a universal dimension – the latter consisting in natural law theory – it does not contribute to a deeper understanding to interprete this combination as a manifestation of the intertwinement of the two natures of Christ.